Housing conditions and long-term care needs of older adults in Ghana: Evidence from the WHO SAGE Ghana Wave 1 - Kofi Awuviry-Newton; Kwamina Abekah-Carter; Kwadwo Ofori-Dua; Razak M. Gyasi; Cindy Nhyira Newton; Williams Agyemang-Duah; Paul Kowal; Pablo Villalobos Dintrans (Public Library of Science (PLoS), 2022)
The present study examined the association between housing conditions and long-term care needs of older adults in Ghana. We used data from 4,920 adults aged ≥50 years that participated in the World Health Organisation's (WHO) Study on adult health and AGEing Ghana Wave 1. Housing conditions were assessed with drinking water, sanitation, cooking conditions and building materials, and long-term care needs were based on WHO Disability Assessment Schedule 2.0. Multivariable logistic regressions modelled the effect of housing conditions on long-term care needs. After full adjustment for all available potential confounders, older adults living in households with unimproved cooking conditions had higher odds of reporting long-term care needs (OR = 6.87, 95%CI: 5.04-9.37) compared to those in improved cooking condition households. Moreover, those in households with unimproved housing materials (OR = 1.27, 95%CI: 1.01-1.72) and those in unimproved sanitation households (OR = 1.26, 95%CI: 1.05-1.54) were more likely to experience long-term care needs after respectively controlling for demographic and health-related covariates. Poor housing conditions are risk factors of long-term care needs in Ghana. Efforts to improve housing conditions may benefit older age functional abilities and unmet long-term care needs.